(untitled) (MAUSAM, 2024)
March and April 2022 months were peculiar with respect to the high temperatures breaking long-period records for India. This study attempts to explain the different causative meteorological factors that led to unprecedented hot weather during the March and April months of 2022. It is interestingly seen in the analysis that the high surface temperature anomaly for the month of March over the North Pole was one of the important factors that hindered the southward progression of the sub-tropical westerly jet stream over India and caused a lesser number of western disturbances to cross over the Indian region. Also, the anticyclonic circulation in the mid-tropospheric levels caused warming over central Pakistan and adjoining regions which caused the high temperatures over Indian regions due to temperature advection by northwesterly winds.